Operations management for dummies - Anderson, Mary Ann (Tantor Media, 2019)
A plain-English guide to improving business operations and increasing efficiency. Operations management is a critical skill for all current and aspiring business leaders. Now, Operations Management For Dummies takes the guesswork out of this often-intimidating subject. Whether you are a professional just promoted into your first operations management job who needs to learn operations fast or your aim is to score your highest in an undergraduate or MBA operations management class, the plain-English, step-by-step information in Operations Management For Dummies gives you the critical toolkit for operations success.
Downloadable audio file
Keywords: Business; Affaires; BUSINESS & ECONOMICS; Production & Operations Management; Downloadable audio books; Audiobooks; Livres audio